Reading the African School Curriculum as an Historical Text:: Educational contexts, policies and practices in Zimbabwe (Yesterday & Today Journal for History Education in South Africa and abroad, 2025)
The current research is a critical rendition of the history of the African school curriculum in Zimbabwe. The paper explores how this curriculum manifested itself from colonial times to the present post-colonial dispensation. Methodologically, we adopt a Kliebardian historical approach to an understanding of the purpose and changing nature of education through a study of the history of education. The study posits that a curriculum may be read through a vertical analysis of changes over time as shaped by varying contexts, policies and practices associated with its development. Thus, the curriculum under review is an historical text. The main conclusions drawn from the study are that in Rhodesia, curriculum goals, content, methods and assessment strategies were crafted to serve the needs of the dominant European group, while African education was perennially under-funded. The post-colonial curriculum was, and is still expected to exorcise the erstwhile colonial elitist educational jinx to serve the needs of the African majority. Regrettably, however, it has been saddled with challenges such as policy and ideological inconsistencies, as well as inadequate financial resources to support change and innovation. We (the authors), therefore, see the study as providing a basis for a critical scrutiny and understanding of the history and purpose of education in Zimbabwe and ipso facto, its possible improvement.
Keywords: African School Curriciulum; Educational Policy Making; History of Education; Kliebardian Historical Approach; Post-colonial; Vertical analysis of changes